The Constitutional Court Decision and Islamic Philanthropy Movements: Analysis of Zakat Organizations Legality in Samarinda - Iswanto, Bambang; Hadinatha, Miftah Faried (Mazahib, 2023)
As the capital of East Kalimantan province, Samarinda city government has adequate access to ensure the Legality of zakat management organizations in its jurisdiction. However, many community-based zakat agencies still carry out their activities without state license. Otherwise, the Constitutional Court Decision Number 86/ PUU-X/2012 obliges these zakat agencies to get the Ministry of Religious Affairs permit based on the National Amil Zakat Agency (BAZNAS) recommendation, in this case, the BAZNAS of Samarinda. This article focuses first on the legal implication of the Court’s decision which confirms the constitutionality of the zakat agencies' licensing requirement in Indonesian Zakat Law. Second, it probes the Samarinda community-based zakat agencies' stance on unlicensed activities and factors affecting their compliance with the Court's decision. Using socio-legal method, this article finds that the Court has established a norm that every zakat management organization must obtain the state's license as long as they operate within the jurisdiction of BAZNAS. Hence, it is considered illegal when community-based zakat agencies in Samarinda manage zakat unlicensed because every corner of the city is arguably within reach of BAZNAS Samarinda operation. Nevertheless, the Court's ruling is not observed by the society in Samarinda because they build their own social construction in implementing the Islamic teaching of zakat. Their stance is mainly influenced by religious motives instead of legal compliance, as well as the hereditary obedience to religious figures. Although many zakat agencies are not licensed, the society always feels benefited and facilitated by their work of collecting and distributing zakat in their region. Keywords: Amil zakat, legality, Constitutional Court, Samarinda